Preserving the integrity of adapted mindfulness-based programmes: an exploratory case study of adapting a mindfulness-based programme to a retail setting - Macdonald, Anne (The University of Edinburgh, 2023)
According to the World Health Organisation, 8% of the global disease from depression is currently attributed to workplace risks (Prüss-Ustün & Corvalan, 2006). In recent years, the pace of demand for making the wellbeing benefits of mindfulness-based programmes in clinical settings available in more mainstream settings such as the workplace, has outstripped the pace of research. There is both a need for more knowledge on the process of adapting mindfulness-based programmes (MBPs) without compromising their integrity and effectiveness (Crane et al., 2016), as well as a need to explore the outcomes and process of adapted programmes, (i.e., what works and why, e.g., Lomas et al., 2017). Underpinned by a pragmatic research philosophy and using a case study design, this thesis aimed to address these needs. A phased approach to adapting an MBP to a retail workplace setting is outlined, with two studies exploring the scoping phase and one single-case design intervention study investigating the implementation and evaluation phase. The overall findings contribute to the fledgling body of knowledge on adapting MBPs in two ways, both of which offer advances to professional mindfulness teaching practice. Firstly, the adaptation process used provides a platform for developing a “compass” for mindfulness teachers to use whilst adapting programmes and protecting their integrity. Secondly, the intervention study findings strengthen the case for workplace MBPs being a facilitator of mental wellbeing and other useful employee behaviour benefits (e.g., interpersonal skills, ability to focus). The programme theory of change and associated theory of action elicited offer a clear support to mindfulness teachers in their articulation of how and why MBPS can benefit a prospective organisation. Whilst the case study approach limits the generalisability of the findings, it paves the way for future research to refine both the adaptation process and the use of a specific theory of change and theory of action for workplace programmes.
Keywords: mindfulness-based programmes; workplace; wellbeing; performance psychology